Bond Strength Behavior for Deformed Steel Rebar Embedded in Recycled Aggregate Concrete - Aseel AbdulAzeez AbdulRidha; Raad Abdulkhudhur; Hussein Al-Quraishi (Journal of Engineering and Technological Sciences, 2021)
This study investigated the bond strength behavior of a deformed steel bar embedded in RAC through an experimental program and numerical analysis. In the experimental work, eighteen push-out specimens were tested. The compressive strength of RAC, the recycled aggregate replacement ratio, the embedded length of the reinforcing bar, the size of the rebar, the concrete cover, and the yield stress of the reinforcing steel bar were the main parameters investigated. The effect of these parameters on bond strength, bond-slip behavior, and modes of failure are discussed. Analysis of the test results indicate that the bond strength in concrete is reduced by 13% when using a specimen constructed from recycled aggregate compared with conventional concrete. The failure modes in a reinforcing bar embedded in RAC representing splitting failure and push-out failure, were similar to those in conventional concrete. The finite element analysis presented in this study was used to analyze forty-four push-out specimens. Through numerical analysis, the bond strength of RAC was related to the 0.57 power function of compressive strength. A design equation for bond strength of reinforcing bars embedded in RAC is proposed. The proposed equation was calibrated through the numerical and experimental results.